(untitled) (Bangladesh Journal of Educational Research, 2026)
Over the last three decades, many educationalists and researchers have provided multiple models of school improvement. In most models, teachers’ quality is recognised as a central feature of the school improvement process. In Bangladesh, the government has, for years, taken various policy initiatives to improve secondary education, but the gap between rural and urban schools remains clearly visible. A lack of quality teachers, insufficient school resources, improper learning environments, and mostly inconsistent policy guidelines are hindering the progress made. In this conceptual paper, the researchers argue that, for school improvement to be effective, policy reforms and change initiatives must focus on the development of teachers’ quality and schools’ capacity equally to manage change, as these two factors are interconnected. To counter these barriers, this paper recommends a multi-level intervention framework. At the policy level, the study proposes targeted financial incentives and decentralised recruitment to improve rural teacher retention. At the school level, it advocates for inter-school collaboration to share limited resources and strengthen change management capacity. Finally, at the classroom level, the paper calls for increasing teacher autonomy and integrating student feedback to adapt national curricula to local rural contexts.